Wick hydroponic cultivation technique as an effort to optimize the use of the yard for the Keranji Guguh community - Ulfia Hasanah; Aan Royfan; Annisha Maharani; Arief Rivansyah; Novita Hardianti; Muhammad Farhan Aswan; Fajri Bushairi; Rika Dianti; Selvia Rahma Dona; Siti Halimah Tusadiah (Universitas Muhammadiyah Magelang, 2023)
The majority of Keranji Guguh Village's residents work in the agricultural sector, which looks after a land area of 805.42 Ha. The product produced is palm oil, while the production of vegetable crops is very low. In addition, the majority of the land near residents' homes is underutilized. This is due to the lack of public interest and knowledge about vegetable cultivation. The purpose of this program is to provide skills for the residents of the village of Keranji Guguh to use the hydroponic system. Hydroponics is a plant cultivation technique that uses water as a growing medium. The activity method is carried out by counseling and practicing how to plant with a hydroponic system. The events held in the village of Keranji Guguh were successful, and the participants could clearly grasp the idea of hydroponic vegetable cultivation using a wick system. As a result, empty yards can be used to grow vegetables.